If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(x+7)-7=7
We move all terms to the left:
2(x+7)-7-(7)=0
We add all the numbers together, and all the variables
2(x+7)-14=0
We multiply parentheses
2x+14-14=0
We add all the numbers together, and all the variables
2x=0
x=0/2
x=0
| 16x-16+4x+26=90 | | 1=x-x^2 | | q^2-2q=15 | | 20y-30=20 | | 7w-6=4 | | 6y+9=15 | | 4=s+2 | | 10=2p/12 | | (14x-22)+(5+55)=90 | | 3x-7=16-2x | | 7x+2=20+x | | -2z+3+z=-12 | | x^2-25x-129=3 | | y=8.55+20 | | 20x-42=6x | | 3w=6w-45 | | h^2-18h=-20 | | 6^-3n=6^3n-1 | | -3.4x-0.3=1.4 | | .2x+4.1=6.3 | | m^2+15m-6=18 | | 2-a=20 | | 3^-3p=1 | | 8=2h+2 | | 1/2x+7=3x-18 | | b^2-27b=60 | | 180-x=1/2((2x+4)+28) | | 2+4x=8.5 | | -f+2+f=8-3f | | 3(3x-4)=+15+45 | | -5-6a=59 | | 3.5z+2.7z=-5 |